Clinical Features and Prognostic Factors of Pediatric Spine Tumors: A Single-Center Experience With 190 Cases. Issue 12 (15th June 2016) - Song, Dianwen; Meng, Tong; Lin, Zaijun; Fan, Tianqi; Yin, Huabin; Li, Bo; Li, Zhenxi; Xu, Wei; Huang, Quan; Zhou, Lei; Li, Song; Yang, Xinghai; et al.
Abstract : Study Design: A retrospective study was performed. Objective: The aim of the study was to illustrate the characteristics of pediatric spine tumors (PSTs) and obtain better insight into therapeutic strategies of such kinds of tumors. Summary of Background Data: PSTs, a heterogeneous group of tumors occurred among pediatric group, are relatively uncommon and rarely reported in the literature. Methods: A retrospective study was performed to analyze clinical features and prognostic factors of patients with PSTs who were treated in our center between 2000 and 2013. Local relapse-free survival (LRFS) and overall survival (OS) rate were estimated using the Kaplan-Meier method to identify potential prognostic factors. Factors with P values of 0.1 or lower were subjected to multivariate analysis by Cox regression analysis. P values of 0.05 or lower were considered statistically significant. Results: A total of 190 patients with PSTs were included in the study. The mean follow-up period was 53.5 months. Of the 190 patients, 127 cases (66.8%) were diagnosed as benign lesions or tumor-like lesions, with 19 cases as aggressive lesions and 44 cases as malignant lesions. Recurrence was detected in 30 patients after initial surgery in our center, whereas death occurred in 24 cases. Implant failure and spinal deformity occurred in 3 and 5 patients, respectively. The statistical analysis suggested that multiple segments involvement (n ≥ 3), aggressive and malignant lesion were independent prognostic factors for LRFS, whereas malignant lesion was the only unfavorable factors for OS. In the subgroup analysis, multiple segments involvement (n ≥ 3) and Enneking stages III were independent factors for LRFS of patients with benign or aggressive lesions. Conclusion: Malignant lesion was significantly associated with decreased OS and LRFS of PSTs, whereas multiple segments involvement (n ≥ 3) and aggressive lesions were significantly associated with LRFS. Level of Evidence: 4 Abstract : Supplemental Digital Content is available in the text